Mesenchymal Stem Cells Coated by the Extracellular Matrix Promote Wound Healing in Diabetic Rats - Linhao Wang; Fang Wang; Liling Zhao; Wenjun Yang; Xinxing Wan; Chun Yue; Zhaohui Mo (Hindawi Limited, 2019)
Objective. To investigate the effects of mesenchymal stem cells (MSCs) coated by the extracellular matrix (ECM) on wound healing in diabetic rats. Methods. Mesenchymal stem cells were cocultured with ECM. Cell viabilities were evaluated using MTT assay. The diabetes model was established using both STZ and high-glucose/fat methods in SD rats. A wound area was made on the middle of the rats' back. MSCs or ECM-MSCs were used to treat the rats. HE staining and CD31 immunohistochemistry were used to detect the skin thickness and angiogenesis. Western blotting and qRT-PCR were conducted to determine the level of VEGF-α, PDGF, and EGF. Results. It was observed that treatment of ECM had no significant effects on the cell viability of ECM-MSCs. Wound area assay showed that both MSCs and ECM-MSCs could enhance the wound healing of diabetic rats and ECM-MSCs could further promote the effects. Both MSCs and ECM-MSCs could enhance angiogenesis and epithelialization of the wounds, as well as the expression of VEGF-α, PDGF, and EGF in wound tissues, while ECM-MSC treatment showed more obvious effects. Conclusion. Mesenchymal stem cells coated by the extracellular matrix could promote wound healing in diabetic rats. Our study may offer a novel therapeutic method for impaired diabetic wound healing.